High nuclear Survivin expression as a poor prognostic marker in pancreatic ductal adenocarcinoma. Issue 7 (27th September 2018) - Zhou, Li; Lu, Jun; Liang, Zhi‐Yong; Zhou, Wei‐Xun; Yuan, Da; Li, Bing‐Qi; You, Lei; Guo, Jun‐Chao; Zhao, Yu‐Pei
Abstract : Background: Survivin, one of the key regulators of mitosis and apoptosis, has long been well recognized to play important biological roles in many neoplasms, including pancreatic ductal adenocarcinoma (PDAC). However, its prognostic value in PDAC remains controversial. Patients and Methods: Nuclear expression of Survivin was detected, using tissue microarray‐based immunohistochemistry, in paired‐tumor and nontumor samples from 306 patients with radically resected PDAC. The staining H scores were further correlated with clinicopathologic features and disease‐specific survival (DSS). Results: Nuclear Survivin expression was much higher in tumor than in nontumor tissues ( P  < 0.001). No significant association between tumoral Survivin expression and clinicopathologic variables was found. For prognosis, high Survivin expression was associated with shortened DSS in all eligible patients and four subgroups, that is, male and nondiabetic patients as well as those with head‐located and G1‐2 tumors, shown by univariate analyses. In addition, a statistically marginal significance was revealed in eight subgroups. For the entire cohort and two subgroups, nuclear Survivin expression was also multivariate identified as an independent predictor for DSS. For patients with G1‐2 tumors, it was the single prognostic marker. Conclusion: Our data suggest an association between high nuclear Survivin expression and poor prognosis in PDAC. However, further confirmation might be necessary.